Implementation of Quizziz Media to Train German Listening Skill of Class X MAN 1 Malang City Students - Agung Perdana Sakti; Lilis Afifah (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2020)
This article aims to describe the process of applying Quizziz media to train German language listening skills of class X MAN 1 Malang City students and student responses to the application of the media. This study used a qualitative descriptive method in conducting research and there were 31 students of class X Religion MAN 1 Malang who became the data sources. Researchers used data collection instruments in the form of questionnaire sheets and observation sheets. The results of this study indicate that the application of Quizizz media to practice listening skills in German in class X Religion MAN 1 Malang runs smoothly and conducively. In addition, students said that Quizizz is an interesting medium to use in learning German in class because this media has attractive features and displays in the form of audio and images.